Ausarbeitung Architekturtheorie - Zandovska, Zane (Journal of A Sustainable Global South, 2024)
The colonial advance had a profound impact on the way of life, resource use, political organization and cultural identity of colonized societies. It manifested itself not only in political structures and economic relationships, but also in architecture and urban planning. This influence led to the emergence of new forms of architecture that merged the styles and practices of the colonizers with local traditions and needs. An interesting example of this is the development of bungalows. The development of bungalows, which originally came  from India,  were not only architectural structures but also symbolic manifestations of colonial power and cultural mixing.  Bungalows, characterized by single-story construction, wide roofs, verandas, and airy floor plans, were popular due to their suitability for tropical climates. These bungalows were often used as homes for British colonial officials, and even after India's independence, they remained widespread in both urban and rural areas. These cottages  gradually altered traditional beliefs about hygiene, cleanliness, and health as well as lifestyle practices. In this context, I will examine the connection between colonization and bungalows by giving  insight into the initial roots and typology of bungalows in order  to understand how architectural forms became witnesses and bearers of colonial history. I will delve deeper about the bungalow  typology  in Ambala cantonment, which despite having similar layouts, this study classifies them according to the fundamental difference in room arrangement.